Remote monitoring of patients with heart failure during the first national lockdown for COVID-19 in France. Issue 3 (29th April 2021) - Ploux, Sylvain; Strik, Marc; Abu-Alrub, Saer; Ramirez, F Daniel; Buliard, Samuel; Marchand, Hugo; Picard, François; Eschalier, Romain; Haïssaguerre, Michel; Bordachar, Pierre
Abstract: Aims: Multiparametric remote monitoring of patients with heart failure (HF) has the potential to mitigate the health risks of lockdowns for COVID-19. We aimed to compare healthcare use, physiological variables, and HF decompensations during 1 month before and during the first month of the first French national lockdown for COVID-19 among patients undergoing remote monitoring. Methods and results: Transmitted vital parameters and data from cardiac implantable electronic devices were analysed in 51 patients. Medical contact was defined as the sum of visits and days of hospitalization. The lockdown was associated with a marked decrease in cardiology medical contact (118 days before vs. 26 days during, −77%, P  = 0.003) and overall medical contact (180 days before vs. 79 days during, −58%, P  = 0.005). Patient adherence with remote monitoring was 84 ± 21% before and 87 ± 19% during lockdown. The lockdown was not associated with significant changes in various parameters, including physical activity (2 ± 1 to 2 ± 1 h/day), weight (83 ± 16 to 83 ± 16 kg), systolic blood pressure (121 ± 19 to 121 ± 18 mmHg), heart rate (68 ± 10 to 67 ± 10 b.p.m.), heart rate variability (89 ± 44 to 78 ± 46 ms, P  = 0.05), atrial fibrillation burden (84 ± 146 vs. 86 ± 146 h/month), or thoracic impedance (66 ± 8 to 66 ± 9 Ω). Seven cases of HF decompensations were observed before lockdown, all but one of which required hospitalization, vs. six during lockdown, all but one of which were managed remotely. Conclusions: The lockdown restrictions caused a marked decrease in healthcare use but no significant change in the clinical status of HF patients under multiparametric remote monitoring. Graphical Abstract: